Evaluating SME Support Programs in Chile Using Panel Firm Data - Tan, Hong (2012)
This paper evaluates small and medium enterprise (SME) support programs in Chile using a firm-level panel for the 1992-2006 period on two groups of firms a treatment group that participated in SME programs and a control group that did not. These unique panel data provide an unprecedented opportunity to address several issues that have plagued impact evaluations of SME programs selectivity bias from observed and unobserved firm heterogeneity, identification of an appropriate control group, and inability to track firms over a long enough period of time for performance outcomes to be realized. Using difference-in-differences models combined with propensity score matching methods, the paper finds evidence that participation in SME programs in Chile is associated with improvements in intermediate outcomes (training, adoption of new technology and organizational practices), and causally with positive and statistically significant impacts on sales, production, labor productivity, wages and exports. The mixed results of previous studies may be attributable in part to the confounding effects of unobserved heterogeneity motivating selection into programs of firms with relatively low productivity levels, and in part to time-effects of program participation occurring in years after the time horizon of most impact evaluation studies.